2017
DOI: 10.1016/j.ahj.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid management in contemporary community practice: Results from the Provider Assessment of Lipid Management (PALM) Registry

Abstract: Background The latest cholesterol guidelines have shifted focus from achieving low-density lipoprotein cholesterol (LDL-C) targets towards statin use and intensity guided by atherosclerotic cardiovascular disease (ASCVD) risk. Methods Statin use and intensity were evaluated in 5,905 statin-eligible primary or secondary prevention patients from 138 PALM Registry practices. Results Overall, 74.7% of eligible adults were on statins; only 42.4% were on guideline-recommended intensity. Relative to primary preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 14 publications
6
46
0
Order By: Relevance
“…Studies that observe real-life practice found similar results; 43 to 58% of patients at a high CV risk and 72 to 78% of patients at a very high risk were still above LDL-C target despite the use of statins [35][36][37]. In the same way, it was observed that a quarter of patients with an indication for treatment were not receiving statins and that the intensity of statin was not sufficient in nearly half of cases [38] underlining the need to be more aggressive in terms of CV risk factor control. However, as not all patients had optimal CV treatment, the rate of CV events could be further reduced in the population studied herein.…”
Section: Discussionmentioning
confidence: 67%
“…Studies that observe real-life practice found similar results; 43 to 58% of patients at a high CV risk and 72 to 78% of patients at a very high risk were still above LDL-C target despite the use of statins [35][36][37]. In the same way, it was observed that a quarter of patients with an indication for treatment were not receiving statins and that the intensity of statin was not sufficient in nearly half of cases [38] underlining the need to be more aggressive in terms of CV risk factor control. However, as not all patients had optimal CV treatment, the rate of CV events could be further reduced in the population studied herein.…”
Section: Discussionmentioning
confidence: 67%
“…There are several reports of inadequate dyslipidemia treatment and the challenge of attaining LDL-C treatment goals in general practice 10,11. Moreover, it has been highlighted in previous research that a significant portion of the statin-eligible population is not receiving the treatment 12. Furthermore, it has been shown that the failure to reduce LDL-C with the recommended LLT has been related to an increased risk of cardiac events 13.…”
Section: Introductionmentioning
confidence: 99%
“…Since a prerequisite for evidence-based management of dyslipidemia is appropriate risk stratification, the discordance in risk assessment could have a substantial bearing on the outcomes. For example, a recent study [ 35 ] showed that only 42.4% of the patients who were recommended for statin therapy were on the recommended statin intensity. In the study, untreated (25.3%) and undertreated (32.3%) patients had significantly higher LDL-C levels than the ones on recommended statin intensity.…”
Section: Discussionmentioning
confidence: 99%